2010
DOI: 10.1055/s-0030-1261893
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Long-Term Treatment of Methylphenidate on Height and Weight of School Age Children with ADHD

Abstract: Stimulant-associated growth deficits in children with attention deficit hyperactivity disorder (ADHD) have long been a concern. We chose 146 school age children diagnosed with ADHD being treated with methylphenidate (MPH) and 29 drug-free ADHD children, and followed them up for 2-4 years. We recorded the changes in height and weight after long-term methylphenidate treatment and analyzed the influence of confounding factors to growth in height, weight, and height velocity. The change of the gap between patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
39
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 7 publications
5
39
0
1
Order By: Relevance
“…9,18 Although studies in the 1970s reported reductions in height in children treated with stimulant medication, 10,19 subsequent studies have been mixed, with some reporting growth reductions 16,[20][21][22] and others finding no significant growth changes. [23][24][25][26] Higher dosages of stimulants may cause more growth attenuation.…”
Section: Discussionmentioning
confidence: 99%
“…9,18 Although studies in the 1970s reported reductions in height in children treated with stimulant medication, 10,19 subsequent studies have been mixed, with some reporting growth reductions 16,[20][21][22] and others finding no significant growth changes. [23][24][25][26] Higher dosages of stimulants may cause more growth attenuation.…”
Section: Discussionmentioning
confidence: 99%
“…In clinical literature, there has been considerable debate about the effects of stimulant therapy on growth rates. There have been reports of the suppression of the normal trajectory of height and weight gain with stimulant treatment (Safer et al, 1972;Zhang et al, 2010). A recent large multicenter study of the effects of extended release formulations of MPH reported significant suppression of growth rates for both height and weight over a 2-year treatment period, persisting over a 3-year follow-up (Swanson et al, 2007).…”
Section: Growthmentioning
confidence: 99%
“…There is evidence for modest growth suppression (Safer et al, 1972;Zhang et al, 2010), although this is far from consistent. Some studies of MPH-treated children have reported reduced growth curves for both height and weight compared with age-matched controls (Swanson et al, 2007), whereas others reported no effects on growth (Biederman et al, 2010).…”
Section: Introductionmentioning
confidence: 97%
“…44,45 Finally, the third objective was to evaluate vulnerability to the reinforcing effects of cocaine after pre-exposure to MPH, using the self-administration paradigm. Overall, no differences were found between groups in the availability of D2/D3 or DATs following exposure to MPH during late infancy.…”
Section: Resultsmentioning
confidence: 99%